The Little Green Data Book 2008 - World Bank (Washington, DC, 2012)
The 2008 edition of the little green data book includes a focus section, four introductory pages that focus on a specific issue related to development and the environment. This year the focus is on the damage from climate change and carbon dioxide emissions. As this focus shows, global warming can have negative effects on agriculture, health, infrastructure, and other economic activities effects that are likely to hit developing countries the hardest. While high-income countries emit more carbon dioxide than developing countries, emissions from developing countries are growing at a faster pace. And emissions per capita in high income countries are still five times higher than in developing countries.